Welcome to Westonci.ca, the place where your questions are answered by a community of knowledgeable contributors. Get detailed answers to your questions from a community of experts dedicated to providing accurate information. Join our platform to connect with experts ready to provide precise answers to your questions in different areas.

Given that the function g is defined by the rule g(x)=3-2x,determine the following

g(a)=


Sagot :

Answer:

The value of g(a) is:

[tex]g(a) = 3 - 2a[/tex]

Step-by-step explanation:

Given

As the function is given by

[tex]g(x)=3-2x[/tex]

To determine

g(a) = ?

Given the function

[tex]g(x)=3-2x[/tex]

substitute x = a in the function

[tex]g(a) = 3 - 2(a)[/tex]

[tex]g(a) = 3 - 2a[/tex]

Therefore, the value of g(a) is:

[tex]g(a) = 3 - 2a[/tex]